2021
DOI: 10.31557/apjcp.2021.22.s1.89
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Valproic Acid on the Class I Histone Deacetylase 1, 2 and 3, Tumor Suppressor Genes p21WAF1/CIP1 and p53, and Intrinsic Mitochondrial Apoptotic Pathway, Pro- (Bax, Bak, and Bim) and anti- (Bcl-2, Bcl-xL, and Mcl-1) Apoptotic Genes Expression, Cell Viability, and Apoptosis Induction in Hepatocellular Carcinoma HepG2 Cell Line

Abstract: Backgrounds: Hepatocellular carcinoma (HCC), Primary liver cancer, is the fifth most common cancer in men. Histone deacetylation causes chromatin condensation resulting in gene silencing and tumorigenesis. These enzymes have become a novel target for the treatment of cancer. Histone deacetylase inhibitors (HDACIs) can reactivate tumor suppressor genes (TSGs) by inhibition of histone deacetylases (HDACs) activity leads to apoptosis induction in cancer cells. Further, these compounds can induce apoptosis through… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 28 publications
1
19
0
Order By: Relevance
“…This is associated with decreased venetoclax binding, increased anti-apoptotic family members associated with BCL-2, changes in the microenvironment, and malfunction of the TP53 pathway [ 103 ]. In the context of chronic venetoclax exposure, it increases MCL1 and BCL-XL expression, both of which have antiapoptotic properties [ 104 ], leading to acquired resistance [ 103 ]. This suggests that drugs may lead to resistance by activating already existent cellular pathways.…”
Section: Resultsmentioning
confidence: 99%
“…This is associated with decreased venetoclax binding, increased anti-apoptotic family members associated with BCL-2, changes in the microenvironment, and malfunction of the TP53 pathway [ 103 ]. In the context of chronic venetoclax exposure, it increases MCL1 and BCL-XL expression, both of which have antiapoptotic properties [ 104 ], leading to acquired resistance [ 103 ]. This suggests that drugs may lead to resistance by activating already existent cellular pathways.…”
Section: Resultsmentioning
confidence: 99%
“…The Bcl-2 family regulates the mitochondrial pathway, which releases both pro-apoptotic (BAX and BAD) and antiapoptotic (Bcl-2 and Bcl-xl) proteins. All of these apoptogenic signals are thought to cause the release of CytC from mitochondria, which then connect with procaspase 9 and APAF1 to create an apoptosome (Rang et al, 2011;Sanaei and Kavoosi, 2021). In the presence of caspase-3 and caspase-9, this apoptosome causes apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies support the role of VPA treatment in the upregulation of p53 and p21. For instance, Sanaei and Kavoosi demonstrated that VPA could downregulate HDAC 1, 2, and 3, and anti-apoptotic genes, including Bcl-2, Bcl-xL, and Mcl-1, and upregulate pro-apoptotic genes, including Bax, Bak, Bim, p53, and p21 in HepG2 cell line, suggesting that VPA induces intrinsic pathway of apoptosis (35). Mechanistically, VPA increases the pro-apoptotic activity of p53 at the mitochondrial membrane by stabilizing its acetyl modifica- tion at lysine 120 (36).…”
Section: Discussionmentioning
confidence: 99%